Contemporary stage art as a performative innovations and provocative cultural and art forms in the postmodernist dimension - Shumakova, Svitlana (My University, 2023)
The author of the article touches ou the issue of performativity, emphasizing that pervasive performa-tivity, as a special cultural phenomenon, has recently been an integral part of modem life. The performative event belongs to the culture of everyday life and exists simultaneously in the space of art and in the space of sociocultural processes - at the intersection of empirical and artistic realities, which implies inseparable sociocul-nual and artistic connections.
Keywords: сценічна практика, stage practice; сценічне мистецтво, performing arts